A new species of Astyanax (Ostariophysi: Characiformes: Characidae) from the upper rio Iguaçu basin, southern Brazil - Ingenito,Leonardo F. S. (2014)
Astyanax eremus, a new species of geographically isolated characid fish, is described from a small tributary of the upper rio Iguaçu basin. The new species belongs to the Astyanax scabripinnisspecies complex and is easily distinguished from its congeners included in this group by its allometric growth of the mouth, which goes from terminal in young individuals to subterminal mouth in larger specimens. Additionally, the new species is distinguished by meristic and morphometric characters. Astyanax eremus presents an evident polymorphism on the traditional character "number of teeth in inner premaxillary row". Comments about that character are provided.